Sharia Stock Transaction Accounting - Sulistian, Windi; Sulistiani, Kania; Montana, Pramudya (JAKI : Jurnal Akuntansi, 2024)
There are several things that need to be considered in Sharia Stock Transaction Accounting. A share can be called a sharia share if the issuer and public company issue it. Because in the articles of association the issuer and public company do not conflict with sharia principles. The journal writing data that we obtained used a qualitative writing method where the information we got came from articles about Sharia Stock Transaction Accounting.